A Molybdenum Disulfide Nanozyme with Charge‐Enhanced Activity for Ultrasound‐Mediated Cascade‐Catalytic Tumor Ferroptosis. (1st February 2023) - Wang, Longwei; Zhang, Xiaodi; You, Zhen; Yang, Zhongwei; Guo, Mengyu; Guo, Jiawei; Liu, He; Zhang, Xiaoyu; Wang, Zhuo; Wang, Aizhu; Lv, Yawei; Zhang, Jian; et al.
Abstract: The deficient catalytic activity of nanozymes and insufficient endogenous H2 O2 in the tumor microenvironment (TME) are major obstacles for nanozyme‐mediated catalytic tumor therapy. Since electron transfer is the basic essence of catalysis‐mediated redox reactions, we explored the contributing factors of enzymatic activity based on positive and negative charges, which are experimentally and theoretically demonstrated to enhance the peroxidase (POD)‐like activity of a MoS2 nanozyme. Hence, an acidic tumor microenvironment‐responsive and ultrasound‐mediated cascade nanocatalyst (BTO/MoS2 @CA) is presented that is made from few‐layer MoS2 nanosheets grown on the surface of piezoelectric tetragonal barium titanate (T‐BTO) and modified with pH‐responsive cinnamaldehyde (CA). The integration of pH‐responsive CA‐mediated H2 O2 self‐supply, ultrasound‐mediated charge‐enhanced enzymatic activity, and glutathione (GSH) depletion enables out‐of‐balance redox homeostasis, leading to effective tumor ferroptosis with minimal side effects. Abstract : An acidic tumor microenvironment‐responsive and ultrasound‐mediated cascade nanocatalyst (BTO/MoS2 @CA) is presented that is made from few‐layer MoS2 nanosheets grown on the surface of piezoelectric tetragonal barium titanate (T‐BTO) and modified with pH‐responsive cinnamaldehyde (CA). The charge‐enhanced enzymatic activity, pH‐responsive CA release‐mediated H2 O2 self‐supply, and glutathione depletion enable out‐of‐balance redox homeostasis, leading to effective tumor ferroptosis.